Effect of adding different levels of Olive Plant Leaves (Olea europea L.) powder to the ration on productive traits of broiler chicks Ross 308 - Abdel Latif Ali, Nihad; Kadhem Alwan, Haider; Abbood Al_saeedi, Tahseen (Journal of Kerbala for Agricultural Sciences, 2017)
This study was conducted at Poultry Farm of Animal production Dept., College of Agriculture, University of AL-Qasim Green to investigate Study the effect of adding different levels of Olive Plant Leaves (Olea europea L.) powder to the ration on productive traits of broiler chicks Ross 308 .Use the 120 broiler chicks Ross 308 day-old were randomly assigned to four treatments (by 3 replicates per treatment 10 chicks per replicate),and treatments were as follows: Treatment for the first (control) without adding olive Leaves powder into the ration, the added treatments were 500, 750 and 100 mg / kg for the first, second and third treatment treatments respectively، The experiment included a study of the following characteristics: body weight, weight gain, feed consumption, feed conversion efficiency and mortality.The results indicated that the addition of olive levels for broiler chickens diet there was not any significant effect on the productive qualities of broiler chickens.